Co construcción de soluciones barriales participativas: caso de estudio barrio chapango-paltas, período 2021-2022 - Pogo Guamán, Luis Eduardo (2022)
The present Curricular Integration Work (TIC) entitled CO-CONSTRUCTION OF PARTICIPATIVE NEIGHBORHOOD SOLUTIONS: CASE STUDY CHAPANGOPALTAS NEIGHBORHOOD, PERIOD 2021-2022 had the general objective of contributing to the Chapango neighborhood in the construction of effective solutions, applying participatory, independent and democratic processes, oriented to meet citizen demands according to the local reality, through the promotion of neighborhood organization and participation; collective diagnosis; and the co-design of solutions to the identified problems. For this purpose, the theory of governance from society was analyzed, as well as other theoretical, conceptual, normative, referential and terminological foundations related to citizen participation at the neighborhood level. At the same time, in order to intervene in the neighborhood, action research was applied, which allowed the development of two roles, that of researcher and participant, for which participatory techniques were applied, such as the Focus group, survey and participant observation. Finally, in order to promote organization and participation in the Chapango neighborhood, it follows that it is necessary to reactivate the directive, the commitment of the community and the creation of a digital space (WhatsApp group) to synchronize issues of organization and participation of the inhabitants, also through the collective diagnosis, observation sheet, survey, prioritization matrix and validation, survey, prioritization matrix and validation it was detected that the central problem lies in the absence of sewerage and to facilitate the solution it is necessary to implement a neighborhood improvement plan, in order to influence the GAD Municipal de Paltas to solve this problem, since it is the exclusive competence of the same the provision of public services.